1967
DOI: 10.1104/pp.42.11.1601
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Biochemistry and Fine Structure of Silica Shell Formation in Diatoms. Chemical Composition of Navicula pelliculosa during Silicon-Starvation Synchrony

Abstract: Summary. iChanges are reported in total cellular organic carbon, nucleic acids, proteins, carfbohydrates, lipids and chlorophylls during the course of silicon-starvation synchrony of Navicula pelliculosa. All constituents increased at the same rate, relative to cel1 number, for 30 hours of exponential growth during which silicon was depleted from the medium. Increase in cell number then stopped. but net synthesis of most components continued for a further 5 to 7 hours before ceasing. Deoxyribonucleic acids and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 20 publications
(15 reference statements)
1
51
0
1
Order By: Relevance
“…Studies aimed at elucidating changes in transcript abundance during nutrient‐limited lipid accumulation often use nitrogen as the limiting nutrient, which is a stressful condition and induces massive cellular changes such as chlorosis and an associated down‐regulation of photosynthesis (Sun et al ., 2013; Abida et al ., 2015; Levitan et al ., 2015). In contrast, short‐term (24 h) silicon starvation has been used as a method to synchronize diatom cultures, and is not generally considered a stressful condition (Coombs et al ., 1967; Hildebrand et al ., 2007; Shrestha et al ., 2012). Silicon starvation‐induced changes in transcript abundance are more likely to reflect the cellular processes that occur as T. pseudonana arrests growth, rather than a response to stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies aimed at elucidating changes in transcript abundance during nutrient‐limited lipid accumulation often use nitrogen as the limiting nutrient, which is a stressful condition and induces massive cellular changes such as chlorosis and an associated down‐regulation of photosynthesis (Sun et al ., 2013; Abida et al ., 2015; Levitan et al ., 2015). In contrast, short‐term (24 h) silicon starvation has been used as a method to synchronize diatom cultures, and is not generally considered a stressful condition (Coombs et al ., 1967; Hildebrand et al ., 2007; Shrestha et al ., 2012). Silicon starvation‐induced changes in transcript abundance are more likely to reflect the cellular processes that occur as T. pseudonana arrests growth, rather than a response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the observed TAG accumulation after 8–12 h of starvation in T. pseudonana is the result of ongoing production of fatty acids with a decrease in cellular requirements for membrane biosynthesis. Other studies have shown that after returning to nutrient‐replete conditions after a short exposure to depleted conditions, diatoms rapidly draw down accumulated lipid stores and resume growth (Coombs et al ., 1967; Valenzuela et al ., 2013). Bioenergetically, it would be more efficient for these stored lipids to be utilized as precursors for membranes or other molecules rather than to be catabolized completely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harvey (1953), Brown and Richardson (1968), Beale and Appleman (1971) and Sheridan (1972) found an inverse proportion between light intensity and chlorophyll a concentrations for algal cells. Steele and Baird (1962), Antia et al (1963), Coombs et al (1967), Eppley (1968), Strickland et al (1969), Hobson and Pariser (1971), Thomas and Dodson (1972) and Peny (1976) showed that deficiency of P, N and Si could lead to a considerable increase in the organic carbon to chlorophyll a ratios. Caperon and Meyer (1972), Eppley and Renger (1974) and Perry (1976) described a negative correlation between specific growth rate and the organic carbon to chlorophyll a ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Surge uptake occurred when intracellular Si level was very low and the maximum uptake rate could be obtained in this process (Conway and Harrison, 1977;Conway et al, 1976). Energy for Si uptake came from respiration (Coombs et al, 1967). Krause et al (2012) pointed that the kinetics parameters of Si uptake (values of V m(Si) and V m(Si) :K m(Si) ) in phytoplankton were coupled with ambient light availability and they increased with the increasing of irradiance at two of the three field stations.…”
Section: Silicon Uptakementioning
confidence: 99%